Peran Mahkamah Konstitusi dalam Penguatan Hak Asasi Manusia Di Indonesia - Saldi Isra (Jurnal Konstitusi, 2014)
The presence of articles on human rights in 1945 affirmed that Indonesia respect of human rights. In order to provide protection and guarantee of human rights, the 1945 Constitution authorizes judicial review to the Constitutional Court. Some  of the verdict of the Court could be used as evidence that the Court conducted to protect and promote human rights. Constitutional Court not only act as guardian of the constitution institutions, but also as the guardian of human rights. Through its judicial review authority, the Constitutional Court appeared as law enforcement agencies that oversee the passage of state power in order not to violate of human rights.